Interactive Media ExploreDigest as an Innovation in Human Digestive System Learning within the Stream of Sustainable Education - Sulistyowati, Dwi Ratna; Suryanti; Widodo, Wahono (Papanda Publisher, 2025)
In support of the national agenda for achieving sustainable development goals—particularly in enhancing the quality of education—the advancement of science and technology plays a pivotal role. The integration of technology into the education sector has significantly transformed the learning landscape in the digital era. This study aims to design and develop interactive media that facilitate engaging, effective, and efficient learning experiences for elementary school students, specifically on the topic of the human digestive system. The research employed the ADDIE development model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. Participants in this development study included subject matter experts, instructional media specialists, and two peers involved in individual trials. Data were collected using validation sheets and structured questionnaires, then analyzed using descriptive qualitative methods. The findings indicate that the interactive media entitled ExploreDigest is deemed feasible and appropriate for supporting science learning in elementary education, as it enhances visual engagement and promotes better comprehension and enthusiasm for learning science.